Learning Apache Pig : explore, manipulate, and analyze big data in the Hadoop ecosystem - Hanlon, Tom (O'Reilly, 2016)
"In this Learning Apache Pig training course, expert author Tom Hanlon will teach you how to explore, manipulate, and analyze data stored on a Hadoop cluster. This course is designed for the absolute beginner, meaning no experience with Pig is required. You will start by learning how to use Pig, then jump into learning about Pig and HCatalog. From there, Tom will teach you about advanced Pig, including Pig scripts, parameters in Pig scripts, and Pig and Oozie. Finally, this video tutorial will teach you about Pig user defined functions and streaming."--Resource description page.